ARTIFICIAL INTELLIGENCE IN HEALTHCARE: BIOETHICAL CHALLENGES AND APPROACHES - Vicini, Andrea (Asian Horizons, 2020)
Artificial Intelligence systems are increasingly introduced in healthcare practice. After defining artificial intelligence (AI) and discussing a few examples of its implementation in healthcare, the essay focuses on ethical challenges and on the currently proposed ethical approach outlined in international documents and centred on principles. Without dismissing such an approach, healthcare practice will benefit from integrating a principle-based approach with a stronger focus on fostering virtuous moral agents and on virtuous contexts that aim at promoting the common good.